Comparative study of understorey birds inhabiting selected logged and virgin lowland forests / Noorul Ezyan binti Nor Hashim - Nor Hashim, Noorul Ezyan (2013)
Community structure of understorey birds can be influenced by habitat structure, microclimate and food resources. Heavy utilization of natural resources in tropical forest for economic purposes has become one of major threat to tropical forest birds. A comparative study on understorey birds inhabiting different habitats of lowland forest was conducted in Ulu Gombak Forest Reserve (UGFR), Selangor and Triang Forest Reserve (TFR), Negeri Sembilan. Mist-netting method was applied to gather information on understorey bird's assemblages inhabiting logged forests (LF) and Virgin Jungle Reserve (VJRs) of the two lowland forests. The effect of seasonal variation such as rainfall and migratory season on understorey birds composition was also studied. A total of 2,370 birds of 120 species were recorded in both study areas after 48 samplings. VJRs were highly diversified compared to LF with domination of primary forest birds such as babblers (Timaliidae) and flycatchers (Muscicapidae). However, increasing number of secondary forest bird such as Little spiderhunter (Arachnothera longirostra) in VJRs raised question on the quality of the reserves. Presence of primary forest birds in logged forests indicating the process of habitat recovery. The results showed that diversity of understorey birds was not influenced by rainfall. Presence of migratory species within the study areas provided evidence of being suitable stopover sites. The information gathered from this work is hoped to support efforts in formulating forest management practices and conservation strategies for wildlife in general and specifically understorey avifauna.